Management of liver metastases of gastrointestinal stromal tumors (GIST) - Vassos, Nikolaos; Agaimy, Abbas; Hohenberger, Werner; Croner, Roland S. (Annals of Hepatology, 2015)
Liver metastases (LM) are crucial prognostic manifestation of gastrointestinal stromal tumors (GIST). With the advent of tyrosine kinase inhibitors (TKI), management of metastatic GIST has radically changed. Long clinical follow-up provides an increased proportion of GIST patients with LM who are candidates for potentially curative therapy.Patients who underwent treatment for liver metastases of GIST between 2000-2009 in our department were included in the study. Mean follow-up was 84 months (range 40-145) months. In retrospective analysis we investigated clinical, macro-/microscopic and immunohistochemical criteria, surgical, interventional and TKI therapy as well.In 87 GIST-patients we identified 25 (29%) patients with metastatic disease. Of these, 12 patients (14%) suffered from LM with a mean age of 60.5 (range, 35-75) years. Primary GIST were located at stomach (n = 4, 33%) or small intestine (n = 8, 67%); all of them expressed CD117 and/or CD34. LM were multiple (83%), distributed in both lobes (67%). They were detected synchronously with primary tumor in 33% and metachronously in 77%. All patients with liver involvement were considered to treatment with TKI. LM were resected (R0) in 4 patients (33%). In recurrent (2/4) and TKI resistant cases, interventional treatment (radiofrequency ablation) and TKI escalation were carried out. During a median follow-up of 84 months (range 30-152), 2 patients died (16.5%) for progressive disease and one patient for other reasons. Nine patients (75%) were alive.Treatment of LM from GIST needs a multimodal approach. TKI-therapy is required at any case. In case of respectability, surgery must be carried out. In unresectable cases or recurrent/progressive disease, interventional treatment or TKI escalation should be considered. Therefore, these patients need to be treated in experienced centres, where multimodal approaches are established.
EVALuna2:6694